2019
DOI: 10.11604/pamj.2019.32.122.16055
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of HBsAg, knowledge and practice of hepatitis B prevention among pregnant women in the Limbe and Muyuka Health Districts of the South West region of Cameroon: a three-year retrospective study

Abstract: Introduction hepatitis B infection is caused by the hepatitis B virus (HBV). HBV is transmitted through sexual intercourse, by exchange of saliva during kissing and also to newborns of infected mothers. In the Global Burden of Diseases 2010, 786,000 deaths were attributed to HBV. Studies in Cameroon, reported the prevalence of HBV as high as 10.1% and 12% among blood donors in hospital blood banks. This study therefore, aims at determining the prevalence of HBsAg, knowledge and practices of pregna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
23
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 25 publications
4
23
2
Order By: Relevance
“…However, our ndings are higher than those of studies done in the east Wolega zone 2.4%, Dawuro 3.5%, Addis Ababa 3%, Eritrea 3.2%, Germany 0.48%, Turkey 2.1%, and China 3.2% [28][29][30][31][32][33][34]. On the other hand, our ndings are lower than those studies done in Dire Dewa 8.4%, Mekele 8%, Hawasa 7.8%, Yirgalem 7.2%, Gambella 7.9%, Harar 6.9%, Tigray 5.5%, Gambia 9.2%, Tazania 8.03%, Cameroon 6.6%, and Ghana 12.9% [16,18,[35][36][37][38][39][40][41][42][43]. There is a variation among the prevalence's of our study with the studies that were conducted around the globe.…”
Section: Discussioncontrasting
confidence: 72%
“…However, our ndings are higher than those of studies done in the east Wolega zone 2.4%, Dawuro 3.5%, Addis Ababa 3%, Eritrea 3.2%, Germany 0.48%, Turkey 2.1%, and China 3.2% [28][29][30][31][32][33][34]. On the other hand, our ndings are lower than those studies done in Dire Dewa 8.4%, Mekele 8%, Hawasa 7.8%, Yirgalem 7.2%, Gambella 7.9%, Harar 6.9%, Tigray 5.5%, Gambia 9.2%, Tazania 8.03%, Cameroon 6.6%, and Ghana 12.9% [16,18,[35][36][37][38][39][40][41][42][43]. There is a variation among the prevalence's of our study with the studies that were conducted around the globe.…”
Section: Discussioncontrasting
confidence: 72%
“…Ephraim, Donko [8] also substantiated that socio-demographic factors did not influence HBV infection among pregnant women in the Ashanti Region. On the contrary, similar studies in Ethiopia, Uganda and Cameroon found significant association between socio-demographic factors, such as marital status, age and occupation and HBV infection among pregnant women [6,10,11]. These findings suggest that risk factors of HBV differ from country to country.…”
Section: Plos Onementioning
confidence: 67%
“…In Nigeria, Anaedobe, Fowotade [12], revealed that pregnant women with multiple sexual partners [6,10,[13][14][15] and those who experienced early sexual debut were more likely to be infected with HBV. Other risk factors include marital status, history of abortion, blood transfusion and surgery, family history of HBV infection, and alcohol intake [10][11][12][13][14][15][16]. However, other studies in sub-Saharan Africa including Ghana, found no significant association between participants' characteristics and HBV positivity [8,9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…17 Meanwhile, some studies had reported lower prevalence of HBV among pregnant women. [18][19][20] The disparity in figures could have been due to differences in the socio-demographic characteristics of the respondents in the respective study settings. The high prevalence of HBV as revealed in the current study and many others portent an emerging public health challenge which requires urgent and concerted efforts from both governmental and non-governmental health agencies to stem the rising tide.…”
Section: Discussionmentioning
confidence: 99%